PEMBERDAYAAN PEREMPUAN MELALUI TEKNOLOGI QUILLING PAPER SEBAGAI USAHA ALTERNATIF BERBASIS LINGKUNGAN DI DESA MARUNGGI KOTA PARIAMAN - Olyy Norita Tetra; Bustanul Arifin; Marniati Salim; Admin Alif; Zulhadjri Zulhadjri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2018)
Empowering women through the improvement of quilling paper handicraft skill withpaper waste material in Desa Marunggi, Kota Pariaman which is the first winner of WestSumatera Dasawisma but this has not been the activity of used paper mill into handicraftproduct with high selling price. The activity begins with environmental sanitation and healthwaste disposal training, advanced waste paper treatment training with quilling papertechnology with modification process that is expensive expensive quilling paper paper withwaste paper. Simple processing and combined with paper waste around the high crafts, artisticand unique products, such as wall decoration, souvenir, multipurpose box, miniature, jar, bag,tissue box, doll and others. The training activities were attended by ± 40 participants attendedby women in PKK and heads of dasawisma groups. This activity is more interesting because itis held handicraft with handicraft goods from hand made. Through this dedication activity, itis hoped that the cooperation of universities and society so that can increase women's resourcesthrough home industry, increase knowledge, skills and is an improvement program of womenparticipation in development.